Changing the Trends in Surgery during the COVID-19 Times: An Experience from the Eastern Uttar Pradesh State, India: CHANGING TRENDS IN SURGERY DURING COVID TIMES - Pandey, Pooja; Bharat, Singh Sandesh; Gupta, Ashutosh (AL-Kindy College Medical Journal, 2022)
Background: The COVID-19 pandemic has an immense effect not only on the social and economic lives of people but also on the surgical lives of surgeons, residents, nursing staff, and patients as well as ground level staff. Amidst this COVID pandemic, emergency surgeries were being done but at a decreased rate, whereas elective cases depended on the will of hospitals, surgeons, and patients. Study aims to promulgate a "Neo–Surgical Check Box" by amalgamating the WHO surgical checklist and the results obtained from the questionnaires.Subjects and Methods: After receiving ethical clearance from the Institute Ethical Committee, an online questionnaire with 50 questions divided into three sections was distributed to 235 surgeons in Uttar Pradesh.Results:Two hundred and eight surgeons had responded, out of which 154 were male and 54 were female. Only 41.4% (86) were actually conducting the surgery. The emergency surgery rate was 60.3%, whereas 18.6% of elective surgeries were done, 11.8% of surgeries were avoided, and the rate of minimal access surgery was 9.3%.Conclusion: The "Neo-Surgical Check Box" will not only increase the number of surgeries per day but also provide protection to the healthcare workers while handling not only COVID-positive patients but also any airborne communicable diseases.